Fremdsprachenlehrwerke in der Frühen Neuzeit Perspektiven – Potentiale – Herausforderungen - Hübner, Julia 1989-; Simon, Horst J. 1967-; Otto Harrassowitz GmbH & Co. KG; Workshop (Episteme in Bewegung, 2021)
The first European textbooks for modern foreign languages were published between the 15th and 17th centuries. These works help to reconstruct the body of linguistic, metalinguistic, and didactic knowledge being imparted in the early modern period. They bring to light practices of multilingualism and didactics at the time, along with the forms and principles of imparting linguistic knowledge. The texts also provide an interesting source for examining historical linguistic variation and question the relationship between linguistic reality and imparted linguistic knowledge. (Translated and adapted from publisher's description.)